Examining the Profound Global Influence of the African Diaspora: A Comprehensive Analysis of Cultural, Social, and Economic Contributions - Sunday Chukwuemeka, Gold (Journal of Central and Eastern European African Studies, 2025)
The African diaspora is a dilatory typology of a history of dispossession, slavery, and oppression. The pain of the Diaspora is not only that of the displacement of more than 400 years, it is one of the spirit that haunts each of the communities of African descent around the world. The paper through analytical and historical methods of research attempts to peel back the layers of this shared agony blocking and as well examine the profound global influence of the African diaspora: a comprehensive analysis of cultural, social, and economic contributions. The transatlantic slave trade left behind one of humanity’s darkest periods. The African diaspora. slavery that saw the forced displacement of millions of Africans, with the human beings treated as property and forced to endure unenviable living conditions in the Americas and elsewhere. The paper notes the far-reaching impact of the African diaspora on the global structures of culture, music, artwork, cooking, language, and religion, where each retains a distinct mark of African tradition. However, the paper also explore wide-ranging social benefits that the African diaspora continues to offer, with particular emphasis on the lasting influence of diasporic peoples through art, economics, political activism, and social movements in the nations that they call home.